2022
DOI: 10.3390/plants11091122
|View full text |Cite
|
Sign up to set email alerts
|

Contact and Fumigant Activities of Citrus aurantium Essential Oil against the Stable Fly Stomoxys calcitrans (Diptera: Muscidae)

Abstract: The stable fly, Stomoxys calcitrans (L.), is a cosmopolitan hematophagous fly of medical and veterinary importance. It is widely considered a major livestock pest that can cause significant economic losses. This study aimed to evaluate the insecticidal activity of Citrus aurantium (L.) essential oil against S. calcitrans based on contact and fumigant toxicity tests. Chemical analysis by gas chromatography-mass spectrometry of the essential oil showed the dominance (93.79%) of limonene in the total essential oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Restello et al [95] evaluated the insecticidal influences of the EO from Tagetes patula on maize weevils and observed its effective influence at concentrations of 10 µL. Moreover, Changbunjong et al [96] indicated that C. aurantium EO exhibits insecticidal activity against the stable fly Stomoxys calcitrans based on contact and fumigant toxicity, which can be achieved as an alternative to synthetic insecticides for controlling this pest, as well as chemical analysis of the essential oil showed the dominance of limonene (93.79%). The present results indicate the high toxicity of C. aurantium and C. reticulata towards aphids.…”
Section: Discussionmentioning
confidence: 99%
“…Restello et al [95] evaluated the insecticidal influences of the EO from Tagetes patula on maize weevils and observed its effective influence at concentrations of 10 µL. Moreover, Changbunjong et al [96] indicated that C. aurantium EO exhibits insecticidal activity against the stable fly Stomoxys calcitrans based on contact and fumigant toxicity, which can be achieved as an alternative to synthetic insecticides for controlling this pest, as well as chemical analysis of the essential oil showed the dominance of limonene (93.79%). The present results indicate the high toxicity of C. aurantium and C. reticulata towards aphids.…”
Section: Discussionmentioning
confidence: 99%
“…Citrus-based essential oils exhibit significant antimicrobial activity against foodborne bacteria and also antioxidant activity to prevent the effects of oxidation; hence, citrus-based essential oils could act as natural preservatives [ 39 , 40 , 41 ]. Furthermore, several studies have reported the high repellent activity [ 42 , 43 , 44 ] and fumigant toxicity [ 45 , 46 ] of citrus-based essential oils against different insects.…”
Section: Introductionmentioning
confidence: 99%
“…As one group of important allelochemicals, volatile components enter the air and soil in similar ways: plants release volatiles into the atmosphere directly [3]; rainwater rinses these components (such as monoterpenes) out of the leaf secretory structures and surface waxes, providing the potential for volatile components into the soil [4]; plant roots could emit herbivore-induced and pathogen-induced volatiles into the soil [5]; these components in the plant litter are also released into the surrounding soil [6]. At present, volatile oils have been increasingly explored for their use in weed and pest management [7][8][9][10][11]. They are found to act by spreading in their gaseous state in the air and by transformation into other states into or onto the soil [3,12], playing an important role in inhibiting plant growth by interspecies interactions and altering the crop-weed plant community [13].…”
Section: Introductionmentioning
confidence: 99%